THE INTENSIFICATION OF THE TECHNOLOGY OF SMOKED SAUSAGES WITH ADAPTED FOOD MODULE - Tatiana Barsukovskaya; Valentin Shipulin; Natalia Lupandina; Anna Savva (Вестник Северо-Кавказского федерального университета)
Studied the possibility of use of adaptedfood module in the production of smoked sausages. The positive impact of demineralised whey in the process of breeding new strains. Active marked decrease in pH, increase in lactic acid microorganisms and the reduced mass loss in model systems of raw sausages with new types of strains during the fermentation process. It is revealed that sodium nitrite, used for the formation and stabilization of the color characteristics is greatly reduced, thus deteriorating the stability of the finished product to oxidative processes during storage is not observed.